Rural emplacements: linking heterotopia, one health and ikigai in central Hokkaido. Issue 1 (2nd January 2022) - Hansen, Paul
Abstract: For over fifteen years the author has conducted fieldwork in a rural area of central Hokkaido. During that time the linkage between individualistic notions of life's meaning, wellness and location or environment have been popular conversation topics among a wide array of interlocutors both native and newcomer. This article briefly outlines three distinct theoretical strands—heterotopia, specifically its concern with emplacement; the One Health paradigm, notably the importance of more-than-human effects and affects; and ikigai, often translated as what gives life meaning. It then disembeds these frames from their common limits and contextual moorings in urban studies and art interpretation, public and veterinary health, and Japanese studies respectively, in order to weave them together via ethnographic biographies that open for comparison concerns regarding health and well-being that vary yet collectively sustain the motivation, sometimes fleeting and often liminal, to remain in rural Japan